Information-Seeking Activity of Rural Health Practitioners - Sandra Matsuda; Joe F. Donaldson (Adult Education Research Conference, 1999)
Qualitative methods were used to identify the information-seeking activity (ISA) of rural health practitioners (non-physicians). Conditions shaping ISA were time, resources, and barriers. The primary strategy used was connecting with resources, particularly people. ISA led to consequences of problem resolution, greater competence, or more questions.